2007
DOI: 10.1002/clc.20171
|View full text |Cite
|
Sign up to set email alerts
|

Multimarker Approach to Risk Stratification Among Patients with Advanced Chronic Heart Failure

Abstract: SummaryBackground: Cardiac troponin I (cTnI), N-terminal pro-B-type natriuretic peptide (NT-proBNP) and highsensitivity C-reactive protein (hsCRP) each predict adverse cardiac events in chronic heart failure (CHF). However, little is known about the utility of these novel biomarkers of CHF in combination.Hypothesis: We hypothesized that simultaneous assessment of the three biomarkers would enable clinicians to stratify risk more effectively among patients with advanced CHF.Methods: Measurements of the biomarke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 14 publications
2
15
0
Order By: Relevance
“…Although cardiac troponin elevations in HF were recognized more than a decade ago, recent developments of high-sensitivity assays have paved the way to better understanding of its role beyond the setting of acute coronary syndromes (ACS). 21 Similar results were obtained in hospitalized patients with AHF (NYHA III or IV and low cardiac output) whereby an increasing number of elevated biomarker levels portend poorer 31-day mortality, while each biomarker also independently predicted adverse clinical outcomes. Ongoing apoptosis and myocardial necrosis may occur as a result of increased myocardial wall stress, while other potential contributors include diminished global (rather than regional) myocardial perfusion and oxygen delivery and ⁄ or diminished renal clearance to name a few.…”
Section: Cardiac-specific Biomarkers Of Ahfsupporting
confidence: 63%
“…Although cardiac troponin elevations in HF were recognized more than a decade ago, recent developments of high-sensitivity assays have paved the way to better understanding of its role beyond the setting of acute coronary syndromes (ACS). 21 Similar results were obtained in hospitalized patients with AHF (NYHA III or IV and low cardiac output) whereby an increasing number of elevated biomarker levels portend poorer 31-day mortality, while each biomarker also independently predicted adverse clinical outcomes. Ongoing apoptosis and myocardial necrosis may occur as a result of increased myocardial wall stress, while other potential contributors include diminished global (rather than regional) myocardial perfusion and oxygen delivery and ⁄ or diminished renal clearance to name a few.…”
Section: Cardiac-specific Biomarkers Of Ahfsupporting
confidence: 63%
“…The combination of troponin I, N-terminal pro-brain natriuretic peptide (NT-proBNP) and CRP was more powerful than a single-marker approach in the risk stratification of major cardiac events in a HF population [64]. In another study, the combination of seven conventional circulating prognostic markers were independent predictors of death and rehospitalization in HF patients [65].…”
Section: Multiple Biomarkersmentioning
confidence: 97%
“…More recently, two different trials performed in small populations suggested the possible additional prognostic power of CRP level measurement, along with cTn and NT-proBNP, in HF patients [109,110]. However, this evidence needs to be reinforced in larger cohorts.…”
Section: The Multimarker Approach (Seementioning
confidence: 98%